2023
DOI: 10.1016/j.ajur.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Daily activities and training experiences of urology residents during the coronavirus disease 2019 pandemic in Indonesia: A nationwide survey

Abstract: Objective To explore the impact of the coronavirus disease 2019 (COVID-19) pandemic on the training experience of urology residents in Indonesia. Methods A cross-sectional study using a web-based questionnaire (SurveyMonkey) involved all registered urology residents in Indonesia. The questionnaire was structured in Bahasa Indonesia, consisted of 28 questions, and divided into three sections: Demographic characteristics, current daily activities, and opinions regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The majority of the students stated a moderate level of EE (10)(11)(12)(13)(14)(15)(16)(17), DP (5)(6)(7)(8)(9)(10)(11), and PA (17)(18)(19)(20)(21)(22)(23) with the mean subscale score of 14.0 ± 6.6, 8.5 ± 6.3, and 20.4 ± 6.6, respectively. About 29.5% and 32.9% of students reported a high level of EE (>17) and DP (>11), respectively, resulting in 17.9% of the burnout prevalence among the students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the students stated a moderate level of EE (10)(11)(12)(13)(14)(15)(16)(17), DP (5)(6)(7)(8)(9)(10)(11), and PA (17)(18)(19)(20)(21)(22)(23) with the mean subscale score of 14.0 ± 6.6, 8.5 ± 6.3, and 20.4 ± 6.6, respectively. About 29.5% and 32.9% of students reported a high level of EE (>17) and DP (>11), respectively, resulting in 17.9% of the burnout prevalence among the students.…”
Section: Resultsmentioning
confidence: 99%
“…Burnout rates among Indonesian residents amid the COVID-19 pandemic have been addressed in previous studies [ 12 , 13 ]. However, the assessment of burnout among Indonesian medical students during the pandemic era was still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The advance of technology enabling quick access to a specific group of respondents has made surveys one of the most frequently used methods of obtaining information. In many countries in Europe and around the world, COVID-19-related surveys have already been conducted among residents of ophthalmology [7,8] and other specialties, such as surgery [9], urology, [10] and anaesthesiology. Although the above-mentioned medical staff are not directly involved in the fight against the pandemic, the surveys revealed that the pandemic had a significant impact on the course of residency and the functioning of their departments [11,12].…”
Section: Introductionmentioning
confidence: 99%